2020
DOI: 10.1109/access.2020.3027881
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Coastline Extraction and Changes Analysis Using Remote Sensing and GIS Technology

Abstract: This study highlights the coastline position changes of Qingdao coastal area from 2000 to 2019, using GIS and remote sensing technologies through Digital Shoreline Analysis System and LANDSAT images. Understanding the coastline movement by suitable method is an important challenge for this extremely dynamic coast. The shoreline changes were statistically measured using three techniques, namely; Linear Regression Rate, End Point Rate and Net Shoreline Movement. For the automatic coastline extraction, different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 48 publications
0
34
0
10
Order By: Relevance
“…Manipulation of hydrological cycles by dam construction, building on beaches, coastal structures such as harbors, beach-protecting structures, jetties, mining of beach sand, and degradation of coastal vegetation are the human activities that could exacerbate coastal changes. Most of the anthropogenic growth was the key reason for the coastline change in Qingdao over 19 years, while the natural factors were the secondary reasons [50]. e overall changes of shorelines along the coast of mainland China increased over the ∼1990-2019 period primarily for land reclamation and quay construction [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manipulation of hydrological cycles by dam construction, building on beaches, coastal structures such as harbors, beach-protecting structures, jetties, mining of beach sand, and degradation of coastal vegetation are the human activities that could exacerbate coastal changes. Most of the anthropogenic growth was the key reason for the coastline change in Qingdao over 19 years, while the natural factors were the secondary reasons [50]. e overall changes of shorelines along the coast of mainland China increased over the ∼1990-2019 period primarily for land reclamation and quay construction [61].…”
Section: Discussionmentioning
confidence: 99%
“…Qingdao is in the southeast of the Shandong Peninsula, at 119°30′-121°00′ east longitude, 35°35′-37°09′ north latitude, bordering the Yellow Sea in the east and south, next to Yantai city in the northeast, bordering Weifang city in the west, and bordering Rizhao city in the southwest (Figure 1), a total area of 11,282 km 2 [50].…”
Section: Study Areamentioning
confidence: 99%
“…Given the real danger that coastal erosion poses to this village, and given the need to prevent coastal risks in a context of climate change, it is essential to characterize the spatial and temporal evolution of the line on the coastline of Lahou-Kpanda (in the south of the Ivory Coast). Remotely sensed data plays an important role in the identification, monitoring and delineation of coastline change at regional or global scales [11][12][13][14]. The availability of multi-band, multi-temporal and multi-sensor images and advances in digital treatment and analysis have allowed scientists to gather information on spatial and temporal changes and on the sensitivity of alterations due to natural and anthropogenic events.…”
Section: Introductionmentioning
confidence: 99%
“…Digital spatial data analysis and mapping, remote sensing, and GIS are widely applied in environmental and natural resources monitoring. Several studies in coastline detection, extraction, and monitoring using satellite imagery have been carried out to find out that this technique is an efficient technique [8]- [10]. The results of their analysis showed that erosion and accretion had occurred along the coastline.…”
Section: Introductionmentioning
confidence: 99%